OVERMACHT: ANALISIS YURIDIS PENUNDAAN PELAKSANAAN PRESTASI AKIBAT PANDEMI COVID-19 - Tauratiya Tauratiya (Fakultas Syariah UINFAS Bengkulu, 2020)
On March 14, 2020, the government of the Republic of Indonesia announced the Covid-19 pandemic as a National Disaster. The whole community was asked to stay at home or work from home. This situation caused the daily activities of the community and government from school, work, trade, and others to become ineffective and delayed. This also affects all national and global corporate activities. Many business entities are disrupted due to the Large-Scale Social Limitation policy, so the company or a person cannot keep their promises as made in the previous agreement. This study examines whether Pandemic Covid-19 can be used as a reason for a person or a company to postpone the performance of achievements because it is considered as an overmacht, and how the legal force. This is a qualitative-library research using a juridical-normative approach. The results showed that overmacht is equated with the term force majeure meaning the state of force, in this case the debtor cannot be held accountable, because the situation occurs outside his control and not because of an element of negligence. The state of overmacht is regulated in the provisions of Article 1244 and Article 1245 of the Civil Code. The Covid-19 pandemic is considered as a forced condition, including the overmacht category, so that it can be used as an excuse for debtors to postpone or not carry out performance according to the agreement, provided that the debtor is able to provide reasons that the failure to fulfill the agreement is not because of them, but because something cannot be predictable, and inevitable.